Three‐Year Outcomes After Temperature‐Controlled Radiofrequency Treatment of Nasal Airway Obstruction - William C. Yao; Randall Ow; Michael J. Sillers; Nathan E. Nachlas; Curtis D. Johnson; Dale Ehmer; Jordan Pritikin; Henry P. Barham (OTO Open)
Abstract Objective To evaluate the long‐term safety and effectiveness of temperature‐controlled radiofrequency (TCRF) treatment of nasal valve collapse (NVC) in patients with nasal airway obstruction (NAO). Study Design This is an extended follow‐up from a prospective, multicenter, single‐arm study. The initial study included participants from 12 sites across the United States who were followed for 24 months and additionally agreed to participate in the extended 36‐month follow‐up. Setting Procedure was performed in‐office with an in‐person follow‐up at 3 months and subsequent follow‐up assessment remotely. Methods Participants received TCRF treatment of only the nasal valve and participated in the extended 36‐month follow‐up. The effect of TCRF treatment was determined by analyzing changes in nasal obstruction symptom evaluation (NOSE) score at each follow‐up compared to the baseline. Results Of the 122 participants in the primary study, 66 participated in the extended 36‐month follow‐up. Compared to baseline, there was a 52.6% decrease in the NOSE score at 36 months (mean change −45.3 [95% CI −52.3 to −38.3]; P < .001), and 83.3% of the participants met the criteria for treatment response at 36 months, as defined by the study endpoint. Post hoc sensitivity analysis of the treatment response for all participants from the time of enrollment was 73.9%. No device or procedure‐related adverse events or serious adverse events were reported in the interval between 24 and 36 months. Conclusion TCRF treatment of only the nasal valve resulted in significant and durable improvement in NAO symptoms through 36 months in participants with NAO due to NVC.